LEAN INCIPIENCE SPIRAL MODEL FOR SMALL AND MEDIUM ENTERPRISES - Chong, Mei Yong; Chin, Jeng Feng; Loh, Wei Ping (International Journal of Industrial Engineering: Theory, Applications and Practice, 2013)
Small and medium enterprises (SMEs) support a balanced local economy by providing job opportunities and industry diversity. However, weak management practices result in suboptimal operations and productivity in SMEs. Few generic lean models conceived with SMEs in mind. In this light, a lean transformation framework for SMEs is conceived. The model is known as lean incipience spiral model (LISM). It aims to effectively introduce lean concepts and later to facilitate sustainable transformation in SME which has limited relevant prior exposure to the concepts. The model builds upon a steady and parsimonious diffusion of lean practices. A progressive implementation is promoted through a spiral life cycle model, where each cycle must undergo four phases. The lean transformation is guided with value stream mapping and a commercial lean assessment tool. Finally, the model was implemented in a suitable case study.